2016
DOI: 10.1016/j.celrep.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

RNF4-Dependent Oncogene Activation by Protein Stabilization

Abstract: SUMMARYUbiquitylation regulates signaling pathways critical for cancer development and, in many cases, targets proteins for degradation. Here, we report that ubiquitylation by RNF4 stabilizes otherwise short-lived oncogenic transcription factors, including β-catenin, Myc, c-Jun, and the Notch intracellular-domain (N-ICD) protein. RNF4 enhances the transcriptional activity of these factors, as well as Wnt- and Notch-dependent gene expression. While RNF4 is a SUMO-targeted ubiquitin ligase, protein stabilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 52 publications
2
84
0
Order By: Relevance
“…In a recent study, 5 we identified that RNF4, a ubiquitin ligase, and the ubiquitin system is part of the machinery involved in stabilization, rather than degradation, of selected short-lived oncoproteins such as b-Catenin, c-Myc, c-Jun, and Notch intracellular domain protein (N-ICD): RNF4 potentiates the transcriptional activity of these oncoproteins, enhances the tumorigenic properties of cancer cells, and is essential for cancer cell survival. Importantly, high RNF4 levels correlate with poor outcome in a subset of cancers.…”
Section: Dysregulated Proteostasis In Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, 5 we identified that RNF4, a ubiquitin ligase, and the ubiquitin system is part of the machinery involved in stabilization, rather than degradation, of selected short-lived oncoproteins such as b-Catenin, c-Myc, c-Jun, and Notch intracellular domain protein (N-ICD): RNF4 potentiates the transcriptional activity of these oncoproteins, enhances the tumorigenic properties of cancer cells, and is essential for cancer cell survival. Importantly, high RNF4 levels correlate with poor outcome in a subset of cancers.…”
Section: Dysregulated Proteostasis In Cancermentioning
confidence: 99%
“…Importantly, high RNF4 levels correlate with poor outcome in a subset of cancers. 5 RNF4 belongs to a small group of RING (really interesting new gene) ubiquitin ligases termed SUMO-Targeted Ubiquitin ligases (STUbL). Conserved from yeast to man, these ligases bind to SUMO chains of SUMOylated proteins via multiple SIM domains at the N-termini of the protein and catalyze their ubiquitylation via the RING domain, thus physically connecting the ubiquitin and SUMO pathways.…”
Section: Dysregulated Proteostasis In Cancermentioning
confidence: 99%
See 3 more Smart Citations